Estimulação Transcraniana por Corrente Contínua (ETCC) na área motora: efeito sobre os sintomas de ansiedade e depressão e a interface com o perfil inflamatório em pacientes com dor crônica e diagnóstico de artrite reumatoide: protocolo para um ensaio clínico randomizado, duplo-cego e controlado por placebo - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Synovite of joints with damage to cartilage and adjacent soft tissues is called rheumatoid arthritis (RA) – an autoimmune disease that causes chronic pain in the affected areas. RA is up to 3 times more prevalent in women, being often associated with anxiety and depression, comorbidities causing psychic suffering and potentiating pain perception, also related to the high risk of suicide among diagnosed patients. The high rates of discontinuation of conventional pharmacological treatments are the predominant factor in the search for new therapeutic approaches for the treatment of anxiety and depression. Transcranial direct current stimulation (tDCS) is a promising, safe and low-cost technique very associative with other therapies. This current induces changes at the subthreshold level and modulates the potential of the neuronal membrane when one neuron receives input from another. When applied to the primary motor cortex (M1) it can induce long-term changes in the synaptic level leading to improvement of neuroplasticity. This study aims to value the effect of tDCS on the symptoms of anxiety and depression, as well as, in a secondary way, aims to evaluate the interference of tDCS on the inflammatory profile, cardiac autonomic behavior and quality of life of patients with rheumatoid arthritis. This is a randomized, double-blind, placebo-controlled clinical trial. The intervention consists in 10 consecutive sessions (1 time a day) applying to tDCS with a 2mA current for 20 minutes. The electrode assembly on the scalp is in accordance with the International Electroencephalogram System 10/20 (EEG) and the anodic electrode is positioned over the area of the primary motor cortex (M1 - C3 or C4) and the cathode electrode on the supraorbital contralateral area (SO - Fp1 or Fp2). The analysis of continuous variables must be described by mean and standard deviation for parametric data and median and interquartile interval for nonparametric data. The evaluation of the effect of tDCS on inflammatory profile, heart rate variability and quality of life must be obtained by the two-way ANOVA model. tDCS is expected to have a greater effect on reducing anxiety and depression symptoms compared to placebo, being able to decrease inflammation and improve the quality of life of volunteers.
Keywords: Doenças autoimunes; Reumatismo; Pessoas depressivas; Transtornos da ansiedade; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE; Artrite Reumatoide; Inflamação; Dor crônica; Neuroestimulação; Ansiedade; Depressão